The Islamic Capital Market Response to the Real Earnings Management - Rita Yuliana; M Nizarul Alim (Universitas Hayam Wuruk Perbanas, 2017)
This study aims to prove the effect of the company's status, i.e membership on the Islamic capital market and the status as suspect firm, as a determinant of real earnings management (REM). REM is conducted by abnormally increasing sales, increasing production and reducing discretionary costs in order to achieve a certain earnings target. This study uses Earnings Distribution Analysis (EDA) technique, which refers to the Prospect Theory (Kahneman & Tversky, 1979) to identify the suspect firms. Suspect firms are companies that have small positive earnings. The samples of this research are companies listed on the Indonesia Stock Exchange in 2011 and 2012. Based on the result of regression analysis, hypothesis testing results show that the suspect firms conduct real earnings management in all three types of activities more aggressively than the non-suspect firms. Furthermore, this study also showed empirical evidence that there are differences in real earnings management actions between companies listed in the Islamic capital market compared to conventional capital markets. Then, this study also showed that the Islamic capital market is more appropriate in response to the REM than the conventional capital market.